2011
DOI: 10.1007/s11434-010-4236-7
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Paleoproterozoic rapakivi granite on the northern margin of the Yangtze block and its geological significance

Abstract: The Huashanguan rapakivi pluton in Zhongxiang, Hubei Province, China, is the first discovered Proterozoic rapakivi pluton in the Yangtze block. Based on field and petrographical observations, a typical rapakivi texture was found in the northern portion of the Huashanguan granitic pluton. Almost all the K-feldspar phenocrysts were round to oval in shape and most had plagioclase coatings known as rapakivi phenocrysts. Alkali feldspars and quartz had two or more generations. Petrochemically, the Huashanguan rapak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(20 citation statements)
references
References 71 publications
1
19
0
Order By: Relevance
“…The ca. 1.86 Ga zircon grains have similar age and Hf isotope compositions with A-type granites (Xiong et al, 2009;Zhang et al, 2011) and mafic dykes in the northern Yangtze Block. Thus, those detrital zircons in Mid-Neoproterozoic sedimentary rocks were most likely derived from the locally exposed Paleoproterozoic mafic-granitic rocks in the northern Yangtze Block.…”
Section: Provenances Of Sediments Across the Mid-neoproterozoic Unconmentioning
confidence: 86%
“…The ca. 1.86 Ga zircon grains have similar age and Hf isotope compositions with A-type granites (Xiong et al, 2009;Zhang et al, 2011) and mafic dykes in the northern Yangtze Block. Thus, those detrital zircons in Mid-Neoproterozoic sedimentary rocks were most likely derived from the locally exposed Paleoproterozoic mafic-granitic rocks in the northern Yangtze Block.…”
Section: Provenances Of Sediments Across the Mid-neoproterozoic Unconmentioning
confidence: 86%
“…Nonetheless, current research indicates that the age of the Quanqitang pluton is 1854 Ma [3,8,14], and the age of the Huanshanguan pluton is 1851 Ma [15]. Hence, both of these plutons are middle-late Paleoproterozic in age, and they share the same tectonic setting associated with rifting of the Columbia supercontinent during the Paleoproterozic.…”
mentioning
confidence: 78%
“…To date within the Yangtze craton, the Quanqitang granite and Huashanguan pluton have been recorded as the oldest K-granites [4,8,15], the age of which are middle Paleoproterozoic (ca. 1850 Ma).…”
Section: Archean Continental Basement Beneath the Yangtze Cratonmentioning
confidence: 99%
“…Peng et al (2009) found a dolerite dyke with similar U-Pb ages around 1.85 Ga and ε Hf (t) values of −6.3 to 0.5 in the Kongling complex, implying that they were derived from partial melting of an enriched mantle source. Zhang et al (2011) reported an A-type granite with a U-Pb age of 1851±18 Ma at Zhongxiang, to the east of the Kongling complex. As shown in Fig.…”
Section: Yangtzementioning
confidence: 99%